Implicações do estudo de mestrado na prática docente - Sandeski, Adnilra Selma Moreira da Silva (Universidade do Vale do Rio do Sinos, 2006)
This work has as focus to investigate the implications of the master study of in the practical teaching of teachers of senior high school and professionalizing education. The research justifies itself while the realization of the master course has the meaning to make possible to the teacher a better professional qualification and a knowledge view that makes possible the incentive to the research in classroom, in view of that the teachers have a crucial contribution to prepare the young, not only to face the future with confidence, but to construct it in determinate and responsible way. The research had as sustentation theories that deal with the graduation of teachers, teaching known, professional development and professional identity the author’s bases are: Paulo Freire, Selma Garrido Pimenta, Antonio Nóvoa, Maurice Tardif, Miguel Arroyo, Maria Izabel da Cunha, among others. To reach the objective of the research, it had been interviewed four teachers of a federal technique school who had carried out study o
Keywords: saber docente; desenvolvimento profissional; formação continuada; professional development; teaching known; continued formation; Ciências Humanas